Area‐Selective Atomic Layer Deposition Using Vapor Dosing of Short‐Chain Alkanethiol Inhibitors on Metal/Dielectric Surfaces. Issue 13 (25th March 2022) - Lee, Jeongbin; Lee, Jeong‐Min; Ahn, Ji‐Hoon; Park, Tae Joo; Kim, Woo‐Hee
Abstract: Area‐selective atomic layer deposition (AS‐ALD) has enormous potential for selective formation of thin films in a bottom‐up additive fashion on predefined areas. Despite significant efforts in a number of AS‐ALD processes using bulky self‐assembled monolayers (SAMs) with long alkyl chains as inhibitor molecules on non‐growth areas, there is increasing interest in achieving selective deposition compatible with complex 3D structures with smaller technology nodes in the semiconductor industry. In this work, a process is introduced that allows selective deposition with short‐chain alkanethiols as vapor‐phase inhibitors. For this purpose, 1‐hexanethiol and 1‐propanethiol are used to selectively deactivate the Cu region relative to the SiO2 region as a model metal/oxide system. Using discrete feeding of both alkanethiols, their blocking capability is explored against subsequent Ru ALD. To improve their blocking ability toward achieving better selectivity for thicker films at higher numbers of ALD cycles, a combined strategy is further demonstrated that involves periodically correcting procedures composed of consecutive "selective lift‐off of residual film moieties" and "regeneration of alkanethiols" to restore the surface‐deactivating capability on the non‐growth areas. Current approaches toward practical enablement of AS‐ALD using short‐chain inhibitors can open up the possibility for advanced bottom‐up nanofabrication compatible with next‐generation nanoelectronic applications. Abstract : An effective strategy to enable an area‐selective atomic layer deposition (AS‐ALD) process using small alkanethiol self‐assembled monolayers (SAMs) with typical lengths of < 1 nm in comparison with conventional SAMs (≈3 nm) is demonstrated. It is worthy to note that combined supercycle strategies that involve selective lift‐off of residual film moieties and restoration of alkanethiols achieve highly selective Ru thin films.